EDUCATIONAL VALUES IN CHILDREN LITETARY WORKS BY MURTI BUNANTA - Roy Raja Sukmanta Meliala; Sahid Teguh Widodo; Slamet Subiyantoro (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2017)
This study aims to see the value of any character education found in children's literature entitled “The Youngest Frog”, “Si Molek”, “Masarasenani and Sun”, and “Tiny Boy” by Murti Bunanta. Children's literature is a literary work written by adults and intended for children. This study used descriptive qualitative intends to understand the phenomenon of what is experienced by the subject of research. This study revealed that the use of dominant character education values can be seen in the value of love peace, hard work, communicative, creative, and curiosity with the amount of data 4 or 13 percentage. Values of character education are manifested in the democratic and religious values.